Extended adjuvant endocrine therapy for women with hormone receptor-positive early breast cancer: A meta-analysis with trial sequential analysis of randomized controlled trials - Xie, Ming; Zhong, Yan; Yang, Yide; Shen, Fang; Nie, Yue (Frontiers in Oncology, 2022)
Objectives The aim of the current study is to explore the association between extended adjuvant endocrine treatment and prognosis of women with hormone receptor-positive (HR+) early breast cancer. Methods Databases including PubMed, Web of Science, Embase and the Cochrane Library databases were electronically searched to identify randomized controlled trials (RCTs) that reported extended endocrine therapy for women with HR+ early breast cancer. The retrieval time was limited from inception to September 2022. Two reviewers independently screened literature, extracted data, and assessed risk bias of included studies. Meta-analysis was performed by using R software Version 4.1.2 and STATA Version 12.0. Results A total of 15 RCTs involving 29497 cases were included. The overall analysis showed that compared with the control, extended adjuvant endocrine therapy increased disease-free survival (DFS) (HR=0.814, 95% CI: 0.720-0.922, 95% PI: 0.556-1.194), overall survival (OS) (HR=0.885, 95% CI: 0.822-0.953, 95% PI: 0.771-1.035), relapse-free survival (RFS) (HR=0.833, 95% CI: 0.747-0.927, 95% PI: 0.575-1.159), distant metastatic-free survival (DMFS) (HR=0.824, 95% CI: 0.694-0.979, 95% PI: 0.300-2.089) and reduced new breast cancer cumulative incidence (NBCCI) (HR=0.484, 95% CI: 0.403-0.583, 95% PI: 0.359-0.654). For adverse events, extended adjuvant endocrine treatment was associated with a significantly higher risk of bone fracture (RR=1.446, 95% CI: 1.208-1.730, 95% PI: 1.154-1.854) and osteoporosis (RR=1.377, 95% CI: 1.018-1.862, 95% PI: 0.347-5.456). Conclusion Our study showed that extended adjuvant endocrine therapy increased DFS, OS, RFS, DMFS, the incidence of bone fracture and osteoporosis, and reduced NBCCI. Systematic Review Registration https://www.crd.york.ac.uk/prospero, identifier (CRD42022351295)